Tajemnice labiryntów. Geneza, znaczenie i perspektywy dla arteterapii - Stępak, Jędrzej (Kultura-Społeczeństwo-Edukacja, 2016)
This article is inspired by private research conducted by the author over the past few years. The study involved more than 600 students of WSE UAM in Poznan and WP WSPiA in Poznan. The article describes metaphor of the labyrinth. Labyrinth and its metaphor is known in cultures and religions for more than 4,500 years and is still strongly present in many. The main purpose of this study is to explore and show psychological, cultural and philosophical significance and importance of the labyrinth and its metaphors in the modern world - especially among young adults. The article is also a prelude to a discussion about the use of the metaphor of the labyrinth in therapy by art – especially horticultural therapy.